2015
DOI: 10.1021/jp512172v
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of Low-Temperature Catalytic Activity of CO Oxidation Driven by Platinum Clusters Directly Bound to Silicon Substrate Surface

Abstract: Studied were cluster-size dependence of catalytic activity of CO oxidation driven by unisized platinum clusters, Pt N (N = 10, 30, and 60), directly bound to a silicon substrate surface. Temperature-programmed desorption measurements were repeated for a given Pt N /Si catalyst with systematic change of the reaction condition. The CO oxidation on the Pt N /Si catalyst is described in a manner similar to the bulk Pt(111) surface; the Langmuir−Hinshelwood mechanism by molecular oxygen activated by the catalyst at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…It has been observed that single atoms (Pd1 or Pt1) are active or not in CO oxidation when they are supported on different substrates. In our experiment we use 12 C 16 O and 18 O2 and we detect 12 C 16 0 18 0 which proves that oxygen molecules have been dissociated before reaction with CO. This observation corresponds to the Langmuir-Hinshelwood (LH) mechanism which has been observed, using molecular beam methods, for Pd (or Pt) extended surfaces [35] and for Pd clusters [31].…”
Section: Reaction Mechanismmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been observed that single atoms (Pd1 or Pt1) are active or not in CO oxidation when they are supported on different substrates. In our experiment we use 12 C 16 O and 18 O2 and we detect 12 C 16 0 18 0 which proves that oxygen molecules have been dissociated before reaction with CO. This observation corresponds to the Langmuir-Hinshelwood (LH) mechanism which has been observed, using molecular beam methods, for Pd (or Pt) extended surfaces [35] and for Pd clusters [31].…”
Section: Reaction Mechanismmentioning
confidence: 71%
“…Third, there is a lack of knowledge about the evolution of the catalytic activity as a function of the number of atoms forming the cluster. This last point can be in principle solved by experiments with size selected deposited clusters [12][13][14][15][16][17]. In 1999, U. Heiz and co-workers studied by temperature programmed reaction (TPR) the CO oxidation of Ptn (n= 5-20) clusters trapped on point defects of the surface on an MgO film [12].…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the error associated to the assumption of spherical shapes in the metal nanoparticles in the estimated particle size, several 3D metal structures, widely observed experimentally for supported metal nanoparticles (Rossi et al 2004 ; Yasumatsu and Fukui 2015 ), have been considering: semi-octahedron, semi-truncated octahedron and truncated pyramid (frustum), as shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, computational chemists, aided by advanced characterisation techniques, have also revealed the key relationship between catalytic activity and shape of the metal nanoparticles due to the selective exposure of different cluster facets and their effect on the adsorption strength of reactants. Indeed, several authors support the fact that the high activity of the metal nanoparticles is directly related to the high concentration of uncoordinated atoms in nano-sized particles (Lemire et al 2004 ), further promoted by specific 3D shapes (Molina et al 2011 ; Yasumatsu and Fukui 2015 ). For example, it is known that the optical response from metal nanoparticles and nanostructures is dominated by surface plasmon generation and is critically dependent on the local structure and geometry such as a range of polyicosahedral shapes or ellipsoids (Rossi et al 2004 ; Bosman et al 2007 ).…”
Section: Introductionmentioning
confidence: 97%
“…[114] One of the physicalmethods for the preparationo fd eposited clusters is mass-selective laser ablation. [115] Al arge number of novel clusters have been prepared by laser ablation:P t [116,117] and Pd [118,119] on MgO, TiO 2 , SiO 2 ,S i, graphite;c lusters of palladium oxides, [120] as well as clusters of Au on Al 2 O 3 , [121] MgO, [13] TiO 2 , [121,122] SiO 2 ; [123] Ag on Al 2 O 3 [124] and tested in CO oxidation, [13,95,116,117] cyclotrimerization of acetylene, [125] epoxidation of propene, [124] ethylene hydrogenation, [126] ando ther reactions.…”
Section: Single-atom Metal Catalystsmentioning
confidence: 99%